2018
DOI: 10.1080/21691401.2018.1492420
|View full text |Cite
|
Sign up to set email alerts
|

Engineering oxygen nanobubbles for the effective reversal of hypoxia

Abstract: Hypoxia, which results from an inadequate supply of oxygen, is a major cause of concern in cancer therapy as it is associated with a reduction in the effectiveness of chemotherapy and radiotherapy in cancer treatment. Overexpression and stabilization of hypoxia-inducible factor 1α (HIF-1α) protein in tumours, due to hypoxia, results in poor prognosis and increased patient mortality. To increase oxygen tension in hypoxic areas, micro- and nanobubbles have been investigated by various researchers. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 39 publications
0
89
0
Order By: Relevance
“…The oxygen concentration was increased in hypoxic areas by using oxygen micro-nanobubbles which were prepared by using different methods. The results indicated the degradation of HIF-1α after the introduction of ONBs [2]. They were also reported to be used in different imaging methods for medical applications.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The oxygen concentration was increased in hypoxic areas by using oxygen micro-nanobubbles which were prepared by using different methods. The results indicated the degradation of HIF-1α after the introduction of ONBs [2]. They were also reported to be used in different imaging methods for medical applications.…”
Section: Introductionmentioning
confidence: 83%
“…This many applications of such tiny and generally ignored object make it worthy to be explored more. Nanobubble has been used for detergent-free cleaning, ultra-sound imaging and intracellular drug delivery like one research has showed their application in drug release in intracellular hyperthermia [9], enhanced drug susceptibility of cancer cells [2], and mineral processing for dispersing Kaolinite and talc in aqueous solution [10] etc.For the last few decades this technology has seen a steep rise. This technology holds really good potential and more and more experimentation and research should be done.…”
Section: Introductionmentioning
confidence: 99%
“…Various combinations of base phospholipids, such as 1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC) and 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) have been used by researchers in combination with various surfactants and emulsifiers, including PEGylated lipids [20,61]. Polyethylene glycol (PEG) is highly hydrophilic with low toxicity, and it is used to improve stability and surface modification and avoid coalescence [11,62,63].…”
Section: Lipid Shellsmentioning
confidence: 99%
“…Electrochemical sensing has also been applied to measure the dissolved oxygen content in a solvent subsequent to the injection of oxygen containing MNBs in a deoxygenated solvent [13]. Fluorescence quenching uses a live cell imaging technique when cells are under hypoxia, and it can be used to evaluate the performance of MNBs to reverse hypoxia [20,76]. Fiber-optic based sensors have also been employed to measure a change in oxygen concentration owing to the MNBs [5].…”
Section: Characterization Techniques For Mnbsmentioning
confidence: 99%
See 1 more Smart Citation